2017
DOI: 10.4274/tjod.33340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pigtail catheter application on obstetric outcomes in in vitro fertilization/intracytoplasmic sperm injection pregnancies following hyperstimulation syndrome

Abstract: Objective:To evaluate the effects of percutaneous pigtail catheter drainage on the outcomes of intracytoplasmic sperm injection (ICSI) pregnancies following moderate or severe ovarian hyperstimulation syndrome (OHSS).Materials and Methods:This retrospective study included 189 patients hospitalized for OHSS following ICSI treatment in a tertiary in vitro fertilization unit between 2006 and 2014. Pigtail catheters were applied in 63 patients; the other 126 patients did not need that treatment. The obstetric repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In case of severe ascites associated with OHSS, ascites drainage is necessary, because severe ascites intra-abdominal pressure is increasing, uterine perfusion decreases, and for some OHSS patients with respiratory compromise due to massive ascites, repeated abdominal paracentesis has been proposed, and it can also improve the respiratory symptoms in patients with pleural effusion. Repeated abdominal paracentesis has the danger of infection, vascular, ovarian and gut injury, and bring more pain and inconvenience to the patient, and abdominal pressure uctuate drastically, Following abdominal paracentesis, in our data, treatment required drainage of uid mostly one to three times, in some cases even six to seven times, Compared with standard paracentesis, central venous catheter is a way of continuous drainage of ascetic uid, its use improves patient care and reduces suffering, studies have reported the use of central venous drainage in the ascites effusion [15][16][17], but our study is the rst in compare the treatment effect of standard paracentesis and central venous catheter. The ndings reported herein indicate that central venous catheter is a convenient way of ascites drainage, avoiding repeated paracentesis, the patients symptoms relieve as soon as the central venous catheter was placed, as long as the catheter was in place, there was no recurrence of symptoms, the abdominal pressure was stable, according to our data the preterm rate of the central venous group was much low than the paracentesis group, when OHSS does occur, and paracentesis is necessary for severe ascites, when repeated attempts seem likely, central venous catheter is a better alternative to repeated abdominal paracentesis in the management of severe ascites of severe OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…In case of severe ascites associated with OHSS, ascites drainage is necessary, because severe ascites intra-abdominal pressure is increasing, uterine perfusion decreases, and for some OHSS patients with respiratory compromise due to massive ascites, repeated abdominal paracentesis has been proposed, and it can also improve the respiratory symptoms in patients with pleural effusion. Repeated abdominal paracentesis has the danger of infection, vascular, ovarian and gut injury, and bring more pain and inconvenience to the patient, and abdominal pressure uctuate drastically, Following abdominal paracentesis, in our data, treatment required drainage of uid mostly one to three times, in some cases even six to seven times, Compared with standard paracentesis, central venous catheter is a way of continuous drainage of ascetic uid, its use improves patient care and reduces suffering, studies have reported the use of central venous drainage in the ascites effusion [15][16][17], but our study is the rst in compare the treatment effect of standard paracentesis and central venous catheter. The ndings reported herein indicate that central venous catheter is a convenient way of ascites drainage, avoiding repeated paracentesis, the patients symptoms relieve as soon as the central venous catheter was placed, as long as the catheter was in place, there was no recurrence of symptoms, the abdominal pressure was stable, according to our data the preterm rate of the central venous group was much low than the paracentesis group, when OHSS does occur, and paracentesis is necessary for severe ascites, when repeated attempts seem likely, central venous catheter is a better alternative to repeated abdominal paracentesis in the management of severe ascites of severe OHSS.…”
Section: Discussionmentioning
confidence: 99%